PENGARUH PERTUMBUHAN EARNING PER SHARE DAN LEVERAGE TERHADAP RETURN SAHAM - Setyowati, Maria; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The aim and this research were to analyse the Earnings Per Share (EPS) influence, and Debt to TotalAssets (DTA) partially and simultaneously against return the share of the company food and beverages that wasregistered in the Indonesian Stock Exchange. The sample of the research was taken was based on 6 companiesfood and beverages, with the period of the research during 5 years (2006-20108) and the analysis technique of thedata used the analysis of multiplied regression.Results of the Test t menujukkan that partially the Earnings Per Share (EPS) variable and Debt toTotal Assets (DTA) had the influence that was significant against return the share, this was based on the level ofthe significance that was produced by each one this variable was smaller than Î±: 5%. The variable that had thedominant influence on return the share was Earnings Per Share (EPS), because of producing the determinationcoefficient partially biggest.F test output results show the value of Fhitung = 18.437 with a significant level of 0.006, indicating that theregression model that tested the Earnings Per Share (EPS) and Debt to Total Assets (DTA) is significant toReturn Shares (RIT), because the sign 0.006 <(Î±) 0.05. This suggests that the Earnings Per Share (EPS) andDebt to Total Assets (DTA) is very well known, if the Earnings Per Share (EPS) and Debt to Total Assets(DTA) may provide hope for investors and companies.Keywords: Stock Return, Earnings Per Share (EPS) and Debt to Total Assets (DTA), Effect of Partial,Simultaneous Effects